KAJIAN GELOMBANG SATU DIMENSI BERDASARKAN HASIL KOMPUTASI NUMERIK - Dwi Sabda Budi Prasetya; Indira Puteri Kinasih (Universitas Pendidikan Mandalika, 2014)
One-dimensional wave problem research has been done based on numerical computation reviews. The one-dimensional wave equation has been completed using the finite difference method. Results of completion based on the results of numerical computation reviews are simulated using MATLAB programming software. The simulation suggests that numerical computation is reliable for solving mathematical equations.